A Framework for the Adoption of Electronic Customer Relationship Management Information Systems in Uganda. Issue 1 (5th December 2017) - Olupot, Charles; Mayoka, Kituyi G.
Abstract: This study proposes a framework for the adoption of Electronic Customer Relationship Management (e‐CRM) information systems in Uganda. Both qualitative and quantitative research methods were used. Primary data were gathered from Small and Medium Enterprises located in 30 districts of Uganda. A self‐administered questionnaire was the main data collection tool. Descriptive statistics were used to analyze data and refine the requirements for adoption of e‐CRM information systems. The findings indicate that for successful adoption of e‐CRM information systems, there should be user sensitization, training and infrastructure. There is also need for top management support and an e‐CRM policy to guide usage. The most important features of e‐CRM information systems were identified as the ability to ensure customer privacy, presence of a Frequently Asked Questions tool, and high speed. The proposed framework was developed based on Thong (1999) Technology Organizational Environmental Management (TOEM), with refined requirements from primary data. The developed framework was validated using a case study. Validation results indicate that the framework is applicable and can help improve the adoption of e‐CRM information systems in Uganda.